Inserção externa e diferenciação econômica de Sergipe: uma análise a partir do índice das vantagens comparativas reveladas (VCR) entre 2000 e 2011 - Santos, Clara de Assis Dantas dos (2013)
The 1990s was marked by deep structural reforms of the Brazilian economy. Trade liberalization can be identified as the launching pad for other structural changes in the economic model which went into effect in the country from there. On one hand, the trade liberalization has created the conditions for the equation of relative prices, acting as an instrument of adjustment between supply and domestic demand, on the other, began to demand a greater effort to attract foreign savings to compensate for the mismatch between demand and supply external, in other words, the internal adjustment generated a strong external imbalance, with the current account deficit. The defense of the argument of comparative advantage was crucial for the purpose of adoption of liberalizing measures in the face of the defense of the country s largest insertion in international trade through competitiveness of productive structures. However, the participation of the regions in foreign trade seems to have reinforced the prevailing pattern before the opening of the economy, which can be attributed to the strong inter-regional economic differentiation. The main objective of the study was to examine the forms of external insertion of the Northeastern economy, highlighting the regional differences and the pattern of trade conducted by the state of Sergipe. For this, we used the index of Revealed Comparative Advantages (RCA). The study showed that the state has VCR into six groups of products, especially food, tobacco and beverages; footwear and leather; and machinery and equipment. In general, the performance of the state revealed the diverse character of the industrial structure, despite the importance of the food sector in total exports.